A study on the potential of yeasts isolated from palm wines to produce flavouring compounds. (June 2020) - Simon Amoikon, Tiemele Laurent; Marcotte, Stéphane; N'Dede Djeni, Theodore; Celaire N'Sa, Koky Marc; Grondin, Cécile; Tinsley, Colin; Casaregola, Serge; Dje, Marcellin Koffi
Abstract: Despite the increasing importance of palm wines as a key element in Ivorian socio-cultural practices, and the high involment of yeasts in the production of these beverages, no studies have been devoted to aroma production of yeasts and their potential uses in biotechnological applications. In this work, aroma profiles of 20 non pathogenic yeast strains (11 from raffia and 9 from ron, representing 13 species) among the 21 yeasts isolated were established using HS–SPME–GC/MS analysis. A total of 50 Volatile Organic Compounds (VOCs) produced by these yeasts were identified and grouped into five main families, namely higher alcohols, aldehydes, ketones, organic acids and esters. Among these VOCs, esters were the most abundant (28 compounds). Some strains produced specific compounds of technological interest which could be used for diverse applications, such as beverages, ice creams, baked goods and desserts and synthetic flavouring ingredient. Among them, Hanseniaspora jakobsenii CLIB 3083 produced the highest number of VOCs. Highlights: Screening of Saccharomycotina yeasts from palm wine for their capacity to produce aroma compounds. Five main families of VOCs were highlighted by HS-SPME-GC/MS. Esters were the most abundantly aroma compounds produced. Hanseniaspora jakobsenii CLIB 3083 produce the highest number of VOCs.